Analisis Efektivitas dan Efisiensi Penggunaan Aset dalam Upaya Meningkatkan Manfaat Ekonomi Anggota - Cinta Melcia Azzahra; Rosti Setiawati (J-Coop : Journal of Co-operative, 2025)
This study aimed to improve the economic benefits of cooperative members through the effectiveness and efficiency of asset utilization. The research was conducted at Kopel BULOG Jabar Consumer Cooperative in Bandung City using a case study method, where data were collected and analyzed in depth. The effectiveness of asset utilization was measured using activity ratios, while efficiency was assessed through operational ratios. Direct economic benefits were analyzed from financial and member perspectives, while indirect economic benefits were measured by calculating the remaining operating results for members. The findings revealed that asset utilization was ineffective, as there was a decline in accounts receivable turnover, inventory turnover, fixed asset turnover, and total asset turnover compared to the previous year. Furthermore, asset utilization was also inefficient, as operational ratios remained stable in the last year. Direct economic benefits, such as services from the Savings and Loan Business and Kopel Mart Business, were experienced by cooperative members, although price advantages were not fully realized. However, indirect economic benefits in the form of the remaining operating results for members also decreased compared to the previous year. These results highlight the need for improved strategies in asset utilization to ensure better economic benefits of cooperative members.